Morbidities Worsening Index to Sleep in the Older Adults During COVID-19: Potential Moderators - Almondes, Katie Moraes de; Castro, Eleni de Araujo Sales; Paiva, Teresa (Frontiers in Psychology, 2022)
Older adults were considered a vulnerable group for the COVID-19 infection and its consequences, including problems with sleep. Aim: To evaluate the prevalence of sleep disorders in older adults, describe their sleep patterns, as well as to analyse if there were any changes in comparison with the period pre-pandemic. Methods: Online survey used for data collection received answers from 914 elderly (age range 65 – 90y), from April to August 2020. Results: 71% of the sample reported a pre-existent sleep disorder, and some of them worsened during the pandemic, especially Insomnia in women and Obstructive Sleep Apnea in men. No difference in sleep duration before and during the pandemic was found, although there was a worsening of some aspects related to sleep, such as sleep quality, sleep efficiency, awakening quality, sleep latency and nocturnal awakenings, especially in the female gender. Educational level influenced sleep latency, indicating higher sleep latency among those with primary education when compared with the ones with PhD. Conclusions: The pandemic had influenced sleep patterns among the elderly, as well as worsening of pre-existent sleep disorders. Female gender and low educational level were considered risk factors for sleep alterations, and high educational level, in its turn, appeared to be a protective factor.